London-east Anglia randomised controlled trial of cognitive-behavioural therapy for psychosis. III: Follow-up and economic evaluation at 18 months. - Kuipers, E; Fowler, D; Garety, P; Chisholm, D; Freeman, D; Dunn, G; Bebbington, P; Hadley, C (1998)
BACKGROUND: A randomised controlled trial of cognitive-behavioural therapy (CBT) for people with medication-resistant psychosis showed improvements in overall symptomatology after nine months of treatment; good outcome was strongly predicted by a measure of cognitive flexibility concerning delusions. The present paper presents a follow-up evaluation 18 months after baseline. METHOD: Forty-seven (78% of original n = 60) participants were available for follow-up at 18 months, and were reassessed on all the original outcome measures (see Part I). An economic evaluation was also completed. RESULTS: Those in the CBT treatment group showed a significant and continuing improvement in Brief Psychiatric Rating Scale scores, whereas the control group did not change from baseline. Delusional distress and the frequency of hallucinations were also significantly reduced in the CBT group. The costs of CBT appear to have been offset by reductions in service utilisation and associated costs during follow-up. CONCLUSIONS: Improvement in overall symptoms was maintained in the CBT group 18 months after baseline and nine months after intensive therapy was completed. CBT may be a specific and cost-effective intervention in medication-resistant psychosis.